Limited effect of preoperative dental clearance on infection prevention in primary or revision hip arthroplasty for high- and low-risk groups - Kazuyoshi Baba; Hidetatsu Tanaka; Ryuichi Kanabuchi; Yasuaki Kuriyama; Daisuke Chiba; Yu Mori; Toshimi Aizawa (Journal of Orthopaedic Reports)
Introduction: This study aimed to evaluate the effectiveness of dental clearance (DC) in reducing the incidence of periprosthetic joint infection (PJI) and surgical site infection (SSI) in patients undergoing primary or revision total hip arthroplasty (THA). Methods: 456 primary and revision THA cases from January 2014 to December 2022 were analyzed. Bilateral THA cases were counted as two joints. From January 2018 onward, all THA patients underwent preoperative DC. PJI risk was assessed using Tan's risk scoring system, where higher scores indicated an increased risk. Patients were classified into high- and low-risk groups based on median risk scores and further divided based on whether they received DC. Incidence of PJI and SSI was recorded at 30 and 90 days post-surgery. Microorganisms identified in PJI cases were documented. Group risk scores were compared using the Wilcoxon rank-sum test, and PJI and SSI incidence rates were compared using Fisher's exact test, with significance at p < 0.05. Results: Among the joints analyzed, 235 underwent DC, while 221 did not. The median risk scores for high-risk groups were 77.1 with DC and 87.6 without DC, showing a significant difference. The low-risk groups had median scores of 23.9 and 23.3 with and without DC, respectively, showing no significant difference. One PJI case occurred in the high-risk without DC group at 30 days post-surgery. Two SSI cases occurred at 30 days and seven at 90 days post-surgery. There was no significant difference in PJI incidence between groups with or without DC at 30 days (P = 0.48). The overall incidence of PJI and SSI at 30 and 90 days showed no significant difference between high- and low-risk groups, regardless of whether DC was performed preoperatively. Conclusion: DC before primary or revision THA did not significantly reduce PJI or SSI incidence in high-risk patients.